Ethylene oxide high-efficiency synthetic material and preparation method and application thereof
By using a catalyst material composed of ruthenium oxide nanoparticles and surface oxidized TiV alloy, the existing problems of complex ethylene oxide preparation methods and environmental pollution are solved, and green, efficient synthesis and high-stability catalyst of ethylene oxide are achieved. .
Patent Information
- Application Number
- CN202411429918.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-14
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-14
AI Technical Summary
The existing ethylene oxide preparation methods are complex, consume fossil energy, generate a large amount of greenhouse gases, and affect the performance and life of the catalyst.
A catalyst material composed of ruthenium oxide nanoparticles and surface oxidized TiV alloy (TiV@TiO2) is used to efficiently synthesize ethylene oxide by using TiV@TiO2 as the first active center and ruthenium oxide nanoparticles as the second active site.
It achieves green and efficient synthesis of ethylene oxide, improves the selectivity and stability of the catalyst, reduces dependence on precious metals, and is suitable for industrial production.
Smart Images

Figure CN119352094A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of electrochemical synthesis, and in particular to a high-efficiency ethylene oxide synthesis material and a preparation method and application thereof. Background Art
[0002] As a broad-spectrum sterilant, ethylene oxide is widely used to disinfect various microorganisms such as bacterial propagules, fungal spores, viruses and spores. It is one of the two mainstream sterilization methods for medical devices, especially disposable medical devices, and is widely used in the sterilization of sterile medical device products at home and abroad.
[0003] The current method for preparing ethylene oxide is mainly ethylene epoxidation, which uses fossil energy as raw material, prepares ethylene through cracking and separation, and then prepares ethylene oxide through selective catalytic oxidation. The process is complicated, has high requirements for reaction equipment, and releases a large amount of carbon dioxide greenhouse gas. In addition, ethylene production of ethylene oxide is a typical exothermic reaction, and the heat released will seriously affect the performance and life of the catalyst. Therefore, it is of great significance to create a new ethylene oxide preparation process and synthesize ethylene oxide in a green and efficient manner. Summary of the invention
[0004] The purpose of the present invention is to provide a catalyst material for efficient synthesis of ethylene oxide, which is composed of ruthenium oxide nanoparticles and surface oxidized TiV alloy (TiV@TiO2). Among them, TiV@TiO2 acts as the first active center to dehydrate the raw material ethanol, and the ruthenium oxide (RuO) nanoparticles act as the second active site to selectively oxidize the ethylene formed by the dehydration of ethanol, so that ethylene oxide can be synthesized efficiently and highly selectively. In addition, the TiO2 oxide layer formed on the surface of the carrier has outstanding acid corrosion resistance, which gives the catalyst higher stability, thereby realizing the green and efficient synthesis of ethylene oxide using ethanol as the raw material.
[0005] To achieve the above objectives, on the one hand, the present invention provides a high-efficiency synthetic material for ethylene oxide, which is composed of a TiV@TiO2 alloy as a first active center and RuO nanoparticles as a second active site, wherein the RuO nanoparticles are uniformly distributed on the surface of the TiV@TiO2 alloy, and the TiV@TiO2 alloy is obtained by surface oxidation of a TiV alloy having a three-dimensional porous structure.
[0006] As a further preferred technical solution of the present invention, the diameter of the RuO nanoparticles is 1-1000 nm.
[0007] As a further preferred technical solution of the present invention, the loading amount of RuO nanoparticles in the ethylene oxide high-efficiency synthetic material is 0.5-20wt%.
[0008] According to another aspect of the present invention, the present invention also provides a method for preparing a RuO / TiV@TiO2 catalyst, comprising the following steps:
[0009] S1. Place the three-dimensional porous TiV alloy in an alkaline solution and then in an acidic solution to remove oxides formed on the surface of the TiV alloy;
[0010] S2, immersing the TiV alloy after the surface treatment in step S1 in an aqueous solution of a ruthenium metal precursor, electroplating, and drying to obtain a Ru / TiV intermediate;
[0011] S3, placing the Ru / TiV intermediate prepared in step S2 in an oxygen-containing atmosphere to oxidize the surfaces of Ru and TiV to obtain a RuO / TiV@TiO2 catalyst, i.e., a highly efficient synthetic material for ethylene oxide.
[0012] As a further preferred technical solution of the present invention, Ti and V metals are used as raw materials, the layer thickness is set to 0.01-0.1 mm, the scanning spacing is set to 0.01-0.1 mm, and the three-dimensional porous TiV alloy in step S1 is obtained by laser melting 3D printing. Furthermore, the 3D printing parameters are optimally set to a layer thickness of 0.03 mm and a scanning spacing of 0.065 mm.
[0013] As a further preferred technical solution of the present invention, in step S1, the alkaline solution is a potassium hydroxide solution and / or a sodium hydroxide solution with a concentration of 1 mol / L-6 mol / L, and the TiV alloy is treated in the alkaline solution for 1 h-24 h; the acidic solution is a hydrochloric acid solution or a sulfuric acid solution with a concentration of 0.2 mol / L-3 mol / L, and the TiV alloy is treated in the acidic solution for 3 h-24 h.
[0014] As a further preferred technical solution of the present invention, in step S2, the concentration of the ruthenium metal precursor aqueous solution is 0.02-1 mol / L, wherein the ruthenium metal precursor is at least one of ruthenium trichloride, terpyridine ruthenium chloride hexahydrate, and ruthenium acetylacetonate.
[0015] As a further preferred technical solution of the present invention, in step S2, the electroplating method is cyclic voltammetry or constant potential deposition, the potential range of the cyclic voltammetry is -0.2 to 0.5 V vs. RHE, and the potential of the constant potential deposition method is -0.1 V vs. RHE.
[0016] As a further preferred technical solution of the present invention, in step S2, the oxygen-containing atmosphere is air, or a mixed gas of oxygen and an inert gas, and the volume fraction of oxygen in the mixed gas is 10%-50%.
[0017] As a further preferred technical solution of the present invention, in step S3, the Ru / TiV intermediate is heated in an oxygen-containing atmosphere at a temperature of 120-240° C. for a reaction time of 0.2-6 hours.
[0018] According to another aspect of the present invention, the present invention also provides an application of a high-efficiency ethylene oxide synthesis material in catalyzing the preparation of ethylene oxide from ethanol.
[0019] By adopting the above technical solution, the present invention can achieve the following beneficial effects:
[0020] (1) The preparation method of the RuO / TiV@TiO2 catalyst of the present invention is simple, the materials are readily available, the cost is low, and it is easy to industrialize and produce.
[0021] (2) The TiV alloy (TiV@TiO2) oxidized on the surface of the RuO / TiV@TiO2 catalyst of the present invention serves as the first active center, and the uniformly distributed nano-ruthenium oxide nanoparticles serve as the second active center. During the catalytic reaction, the TiO2 formed on the surface of the TiV alloy can catalyze the dehydration of ethanol molecules, and the formed ethylene is transferred to the second active center ruthenium oxide for selective oxidation, which can efficiently synthesize ethylene oxide and improve the selectivity of ethylene oxide.
[0022] (3) In the RuO / TiV@TiO2 catalyst of the present invention, the TiO2 oxide layer formed on the surface of the carrier has outstanding acid corrosion resistance, so that the RuO / TiV@TiO2 catalyst exhibits excellent stability.
[0023] (4) The RuO / TiV@TiO2 catalyst of the present invention does not use precious metals, has the advantages of low cost and easy operation, and can be mass-produced. It exhibits excellent catalytic activity and stability in the electrochemical synthesis of ethylene oxide using ethanol as a raw material. BRIEF DESCRIPTION OF THE DRAWINGS
[0024] The present invention will be further described in detail below in conjunction with the accompanying drawings and specific embodiments.
[0025] Figure 1 This is a scanning electron microscope photograph of the RuO / TiV@TiO2 catalyst obtained in Example 1, magnified 50,000 times.
[0026] Figure 2 This is the electrochemical mass spectrometry (DEMS) diagram of RuO / TiV@TiO2 obtained in Example 1 when catalyzing the preparation of ethylene oxide.
[0027] Figure 3 This is a performance diagram of the catalytic activity and selectivity of RuO / TiV@TiO2 obtained in Example 1 when catalyzing the preparation of ethylene oxide.
[0028] Figure 4This is a schematic diagram of the principle of catalyzing ethanol to ethylene oxide using RuO / TiV@TiO2 obtained in Example 1.
[0029] Figure 5 This is a catalytic stability curve of RuO / TiV@TiO2 obtained in Example 1.
[0030] The purpose, features and advantages of the present invention will be further described with reference to the accompanying drawings in conjunction with the embodiments. DETAILED DESCRIPTION
[0031] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0032] Unless otherwise defined, the technical terms used in the following examples have the same meanings as those generally understood by those skilled in the art to which the present invention belongs. The test reagents used in the following examples, unless otherwise specified, are all conventional biochemical reagents; the experimental methods, unless otherwise specified, are all conventional methods.
[0033] Embodiment 1:
[0034] A method for preparing an ethylene oxide high-efficiency synthetic material is specifically carried out according to the following steps:
[0035] (1) TiV alloy synthesis and surface treatment
[0036] Selective laser melting 3D printing was performed on the SLM DiMetal-100H equipment. The parameter settings were: layer thickness, scanning spacing, scanning speed, and laser power were 0.03 mm, 0.065 mm, and 1100 mm s, respectively. -1 and 170W, the feed ratio (mass ratio) of Ti and V metal is 1:1. The three-dimensional porous TiV alloy obtained by 3D printing was first placed in a 2mol / L potassium hydroxide solution and stirred. After stirring for 12 hours, it was quickly transferred to a 2mol / L hydrochloric acid solution and continued to be treated for 6 hours to remove the oxide formed on the surface of the TiV alloy;
[0037] (2) Preparation of Ru / TiV intermediate
[0038] According to the ruthenium oxide loading of 6%, 0.1g of ruthenium trichloride was weighed and put into ultrapure water to prepare a ruthenium metal precursor solution with a concentration of 0.1mol / L. The surface-treated TiV alloy was completely immersed in the ruthenium trichloride aqueous solution, with Ag / AgCl as the reference electrode, Pt wire as the counter electrode, and TiV alloy as the working electrode. Electrochemical deposition was performed by cyclic voltammetry in the potential range of -0.2 to 0.5V vs. RHE, with a scan rate of 10mV / s and a scan number of 2000 circles. The electroplated sample was dried to obtain a Ru / TiV intermediate.
[0039] (3) Preparation of RuO / TiV@TiO2 catalyst
[0040] The Ru / TiV intermediate is placed in an oxygen / nitrogen mixed gas with an oxygen volume fraction of 20% and heated at a temperature of 250°C for 2 hours to form a surface oxide layer on the TiV alloy and oxidize metallic ruthenium into ruthenium oxide to obtain a RuO / TiV@TiO2 catalyst.
[0041] The RuO / TiV@TiO2 catalyst prepared in Example 1 was tested as follows:
[0042] 1) SEM (Scanning Electron Microscope) Test of Catalyst
[0043] The results of the test using a scanning electron microscope at a magnification of 50,000 times are as follows Figure 1 As shown. Figure 1 It can be seen from the scanning electron microscope image that ruthenium oxide particles with a particle size of about 20-500 nanometers are evenly distributed on the TiV@TiO2 surface, which is very beneficial to the adsorption and oxidation of reaction intermediates.
[0044] 2) The RuO / TiV@TiO2 catalyst prepared in Example 1 was tested for its performance in catalyzing ethanol to ethylene oxide:
[0045] The working electrode was placed in a mixed electrolyte of 0.1 mol / L HClO4 and 2 mol / L ethanol. A three-electrode system was used, with the electrode prepared in step (3) as the working electrode, the Ag / AgCl electrode as the reference electrode, and the Pt wire as the auxiliary electrode. Cyclic voltammetry was performed on an electrochemical workstation (CHI660d, Shanghai Chenhua Instrument Co., Ltd.) with a scanning potential of 1.0 to 2.5 vs. RHE and a scanning rate of 10 mV / s. The reaction products were recorded using a mass spectrometer. The results are shown in FIG. Figure 2 Then, the reaction was carried out at 2.0V vs. RHE, and the product composition and content were detected by mass spectrometry after 1 hour. Figure 3 As shown. Figure 2 and Figure 3It can be seen that the catalyst prepared in Example 1 produces no other products except ethylene oxide in the process of catalyzing ethanol to ethylene oxide, and the selectivity is 100%. In addition, ethanol can be completely converted into ethylene oxide after one hour of reaction, and the conversion rate is 100%, indicating that TiV@TiO2 has excellent performance in dehydrating ethanol and RuO in catalyzing ethylene epoxidation to ethylene oxide.
[0046] The mechanism of ethanol to ethylene oxide catalyzed by RuO / TiV@TiO2 Figure 4 As shown in the figure, ethanol is first dehydrated on the Lewis acid TiO2 surface formed on the TiV carrier surface to generate ethylene, and then ethylene is transferred to the RuO surface for ring-opening oxidation to generate ethylene oxide. Since the activation energy for breaking the first carbon-carbon bond in the ethylene double bond is small, while the activation energy for breaking the second carbon-carbon bond is large, ethylene is oxidized to ethylene oxide through ring-opening on the ruthenium oxide surface, and will not be completely oxidized to carbon dioxide.
[0047] 3) Stability test of catalyst RuO / TiV@TiO2
[0048] The test conditions for catalyzing ethanol to ethylene oxide were the same, that is, in a three-electrode system, using a constant potential method, and testing the current-time curve of the catalyst at 2.0 V vs. RHE. The results are as follows Figure 5 As shown. Figure 5 The stability test results show that after 100 hours of reaction, there is no obvious change in the reaction performance, indicating that the catalyst RuO / TiV@TiO2 has excellent stability. This is due to the outstanding acid corrosion resistance of the TiO2 oxide layer formed on the surface of the carrier, which greatly improves the overall stability of the catalyst.
[0049] Embodiment 2:
[0050] (1) TiV alloy surface treatment
[0051] The three-dimensional porous TiV alloy was first placed in a 1 mol / L mixed solution of potassium hydroxide and sodium hydroxide and stirred for 8 hours, and then quickly transferred to a 1 mol / L sulfuric acid solution and continued to be treated for 5 hours to remove the oxide formed on the surface of the TiV alloy;
[0052] (2) Preparation of Ru / TiV intermediate
[0053] According to the ruthenium oxide loading of 10wt%, 0.18g of ruthenium trichloride and ruthenium acetylacetonate mixed sample was weighed and placed in ultrapure water to prepare a ruthenium metal precursor solution with a concentration of 0.08mol / L. The surface-treated TiV alloy was completely immersed in the ruthenium trichloride and ruthenium acetylacetonate aqueous solution, and Ag / AgCl was used as the reference electrode, Pt wire was used as the counter electrode, and TiV alloy was used as the working electrode. Electrochemical deposition was performed at a constant potential of -0.1V vs.RHE for 30 minutes. The electroplated sample was dried to obtain a Ru / TiV intermediate.
[0054] (3) Preparation of RuO / TiV@TiO2 catalyst
[0055] The Ru / TiV intermediate is placed in air and heated at 220°C for 4 hours, so that the TiV alloy forms a surface oxide layer and the metallic ruthenium is oxidized into ruthenium oxide to obtain a RuO / TiV@TiO2 catalyst.
[0056] Example 3
[0057] (1) TiV alloy surface treatment
[0058] The three-dimensional porous TiV alloy was first placed in a 2 mol / L sodium hydroxide solution and stirred for 8 hours, and then quickly transferred to a 2 mol / L hydrochloric acid solution and treated for another 8 hours to remove the oxide formed on the surface of the TiV alloy.
[0059] (2) Preparation of Ru / TiV intermediate
[0060] According to the ruthenium oxide loading of 12wt%, 0.18g of ruthenium trichloride and terpyridine ruthenium chloride hexahydrate were weighed and put into ultrapure water to prepare a ruthenium metal precursor solution with a concentration of 0.12mol / L. The surface-treated TiV alloy was completely immersed in the ruthenium trichloride and terpyridine ruthenium chloride hexahydrate aqueous solution, with Ag / AgCl as the reference electrode, Pt wire as the counter electrode, and TiV alloy as the working electrode. Electrochemical deposition was performed by cyclic voltammetry in the potential range of -0.2 to 0.5V vs. RHE, with a scan rate of 10mV / s and a scan number of 2000 circles. The electroplated sample was dried to obtain a Ru / TiV intermediate.
[0061] (3) Preparation of RuO / TiV@TiO2 catalyst
[0062] The Ru / TiV intermediate was placed in an oxygen / argon mixed gas with an oxygen volume fraction of 15% and heated at a temperature of 220°C for 3 hours to form a surface oxide layer on the TiV alloy and oxidize metallic ruthenium into ruthenium oxide to obtain a RuO / TiV@TiO2 catalyst.
[0063] Referring to the test method of Example 1, the catalysts prepared in Examples 2 and 3 were tested for catalytic ethanol to ethylene oxide and stability under the same conditions. The test results showed that the catalytic performance and stability of the catalysts prepared in Examples 2 and 3 were similar to those of the catalyst prepared in Example 1. The selectivity of the catalyst prepared in Example 2 was 100%, the conversion rate was 99%, and the performance did not significantly decay after 100 hours of continuous reaction; the selectivity of the catalyst prepared in Example 3 was 100%, the conversion rate was 98.6%, and the performance did not significantly decay after 100 hours of continuous reaction.
[0064] Although specific embodiments of the present invention are described above, those skilled in the art should understand that these are merely examples and that various changes or modifications may be made to the embodiments without departing from the principles and essence of the present invention. The scope of protection of the present invention is limited only by the appended claims.
Claims
1. A high-efficiency synthetic material of ethylene oxide, characterized in that: The invention comprises a TiV@TiO2 alloy as a first active center and RuO nanoparticles as a second active site. The RuO nanoparticles are uniformly distributed on the surface of the TiV@TiO2 alloy. The TiV@TiO2 alloy is obtained by surface oxidation of a TiV alloy with a three-dimensional porous structure.
2. The ethylene oxide high-efficiency synthetic material according to claim 1, characterized in that: The diameter of the RuO nanoparticles is 1-1000 nm.
3. The ethylene oxide high-efficiency synthetic material according to claim 1, characterized in that: The loading amount of RuO nanoparticles in the ethylene oxide high-efficiency synthetic material is 0.5-20wt%.
4. A method for preparing the ethylene oxide high-efficiency synthetic material according to any one of claims 1 to 3, characterized in that: The following steps are involved: S1. Place the three-dimensional porous TiV alloy in an alkaline solution and then in an acidic solution to remove oxides formed on the surface of the TiV alloy; S2, immersing the TiV alloy after the surface treatment in step S1 in an aqueous solution of a ruthenium metal precursor, electroplating, and drying to obtain a Ru / TiV intermediate; S3, placing the Ru / TiV intermediate prepared in step S2 in an oxygen-containing atmosphere, so that the TiV alloy forms a surface oxide layer, and the metallic ruthenium is oxidized to ruthenium oxide, thereby obtaining a RuO / TiV@TiO2 catalyst, which is a highly efficient synthetic material for ethylene oxide.
5. The method for preparing the ethylene oxide high-efficiency synthetic material according to claim 4, characterized in that: In step S1, the alkaline solution is a potassium hydroxide solution and / or a sodium hydroxide solution with a concentration of 1 mol / L-6 mol / L, and the TiV alloy is treated in the alkaline solution for 1 h-24 h; the acidic solution is a hydrochloric acid solution or a sulfuric acid solution with a concentration of 0.2 mol / L-3 mol / L, and the TiV alloy is treated in the acidic solution for 3 h-24 h.
6. The method for preparing an ethylene oxide high-efficiency synthetic material according to claim 4, characterized in that: In step S2, the concentration of the ruthenium metal precursor aqueous solution is 0.02-1 mol / L, wherein the ruthenium metal precursor is at least one of ruthenium trichloride, terpyridine ruthenium chloride hexahydrate, and ruthenium acetylacetonate.
7. The method for preparing an ethylene oxide high-efficiency synthetic material according to claim 4, characterized in that: In step S2, the electroplating method is cyclic voltammetry or constant potential deposition. The potential range of the cyclic voltammetry is -0.2 to 0.5 V vs. RHE, and the potential of the constant potential deposition is -0.1 V vs. RHE.
8. The method for preparing an ethylene oxide high-efficiency synthetic material according to claim 4, characterized in that: In step S2, the oxygen-containing atmosphere is air, or a mixed gas of oxygen and an inert gas, and the volume fraction of oxygen in the mixed gas is 10%-50%.
9. The method for preparing an ethylene oxide high-efficiency synthetic material according to claim 4, characterized in that: In step S3, the Ru / TiV intermediate is heated in an oxygen-containing atmosphere at a temperature of 120-240° C. for a reaction time of 0.2-6 hours.
10. Use of the high-efficiency synthetic material for ethylene oxide according to any one of claims 1 to 3 in catalyzing the preparation of ethylene oxide from ethanol.
Citation Information
Patent Citations
Preparation method and application of efficient titanium dioxide nanosheet flower loaded Ru catalyst
CN117654494A
Stable alkylene oxide catalysts
EP0480537A1
Process for preparing catalyst
US20140005039A1